Implementasi Metode Six Sigma Untuk Menurunkan Cacat Produk Pada Ukm Onetixs - Isra Hidayat; Khamaludin Khamaludin; Mutia Amyranti (Universitas Islam Syekh Yusuf Tangerang, 2023)
Product quality is a determining factor in customer satisfaction and trust in the products produced. Product defects can cause losses to convection convection. Therefore, this study aims to implementation of Six Sigma method to reduce product defects in Onetixs SMEs. Five stages are used to improve product quality in Onetixs convection, namely Define, Measure, Analyze, Improve, and Control (DMAIC). The results of research on Onetixs convection obtained the type of defect in Onetixs shoes based on the pareto diagram of the highest defects caused by glue stains. Another type of defect is caused by non-sticky soles, and poorly sewn seams. Of the 1040 samples observed, there were 146 defective products caused by 30% non-adhesive sole defects, 38% glue stain defects, and 32% untidy seam defects. Furthermore, the DPMO value of attribute data obtained is 46795 and is at the level of 3.18 sigma. Based on the causes of defects obtained from the fishbone diagram, the proposed improvements given to reduce defects due to glue stains are to improve the quality of work during the shoe gluing process, pay attention to the quality of the glue mixture, pay attention to the quality of the mixture of glue and tools used for gluing, improve the method of gluing, periodically check shoesKeywords: Fishbone Diagram, Pareto Diagram, Quality, Six Sigma